Burundi : 2012 Article IV Consultation and First Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria: Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burundi. (IMF Staff Country Reports; Country Report ;, 2012)
This 2012 Article IV Consultation highlights that despite a difficult economic and social context, Burundi has made steady, though uneven, progress in implementing its Extended Credit Facility (ECF)-supported economic reforms. Real GDP growth is estimated to have increased to 4.2 percent in 2011. The medium-term macroeconomic outlook is challenging. Risks emanate from a delicate social situation given persistent shocks and the high cost of living. Executive Directors have emphasized the importance of pursuing public financial management reforms to foster greater transparency and accountability, and to strengthen institutional capacity.